2008
DOI: 10.1007/s00520-007-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

The use and toxicity of steroids in the management of patients with brain metastases

Abstract: There is considerable variation in the prescribing practices even within a single institution, with many patients receiving high dose of steroids for considerable periods of time and developing related side effects. Strategies to reduce the amount and length of steroids may result in improved therapeutic ratio; we are currently accruing onto such a trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 15 publications
(52 reference statements)
1
71
0
2
Order By: Relevance
“…The literature addressing the use of dexamethasone for adult patients with brain tumours is limited and conflicting, and primarily describes patients with brain metastases. In a review describing the prescribing practices of oncologists and palliative care specialists for their patients with brain metastases, Sturdza and colleagues 8 reported that 45% of surveyed physicians routinely prescribe dexamethasone at a fixed dose of 16 mg daily for Of studies with specific details on dexamethasone dosing (n = 4), 2 used 16 mg daily; 1 used 2 mg 4 times daily; and 1 used 10 mg/m 2 daily. 5 Studies reported tapering the dose as tolerated after wbrt.…”
Section: Question 2: Dosingmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature addressing the use of dexamethasone for adult patients with brain tumours is limited and conflicting, and primarily describes patients with brain metastases. In a review describing the prescribing practices of oncologists and palliative care specialists for their patients with brain metastases, Sturdza and colleagues 8 reported that 45% of surveyed physicians routinely prescribe dexamethasone at a fixed dose of 16 mg daily for Of studies with specific details on dexamethasone dosing (n = 4), 2 used 16 mg daily; 1 used 2 mg 4 times daily; and 1 used 10 mg/m 2 daily. 5 Studies reported tapering the dose as tolerated after wbrt.…”
Section: Question 2: Dosingmentioning
confidence: 99%
“…The presence or absence of symptoms, the types of symptoms, the types of neurologic deficits, and the degree of edema on imaging were all factors cited by the physicians who chose to prescribe a dose other than 16 mg daily 8 . In an accompanying chart review of 88 patients with brain metastases, the authors reported that, of patients treated with dexamethasone, 91% of those receiving 16 mg or more daily and 65% of those receiving less than 16 mg daily experienced at least one side effect ( p=0.006) 8 .…”
Section: Question 2: Dosingmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Sturdza et al 27 surveyed 38 oncologists at a single large cancer center who managed patients with brain metastases to document the use of steroids and the frequency of their side effects. Ninety percent of physicians responded to the survey.…”
Section: Steroidsmentioning
confidence: 99%
“…Side-effects include myopathy, weight gain, osteoporosis, hyperglycemia, and mood or personality changes. [9][10][11] Dexamethasone doses above 24 mg in malignant spinal cord compression are associated with serious acute gastrointestinal toxicity. 1 12 Proximal myopathy has been reported in 10-60% of brain metastases patients on corticosteroids for more than 3 weeks for cerebral edema, and high doses were related to cushingoid features and steroid-induced hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%